Respuesta :

When an exponent is multiplied directly into another exponent, you multiply the exponents.

For example:

[tex](x^{2})^5=x^{2(5)}=x^{10}[/tex]

[tex](x^{4})^3=x^{4(3)}=x^{12}[/tex]

[tex](x^{3}y^{2} )^2=x^{3(2)}y^{2(2)}=x^6y^4[/tex]


When an exponent is negative, you move it to the other side of the fraction to make the exponent positive.

For example:

[tex]x^{-2}[/tex] or [tex]\frac{x^{-2}}{1} =\frac{1}{x^2}[/tex]

[tex]\frac{1}{y^{-3}} =\frac{y^3}{1}[/tex] or y³



[tex](p^{10} r^{-5})^{\frac{1}{5}}=p^{10(\frac{1}{5})}r^{-5(\frac{1}{5})}=p^{\frac{10}{5}} r^{\frac{-5}{5}}=p^2r^{-1}=\frac{p^2}{r^1}=\frac{p^2}{r}[/tex]


ACCESS MORE